A novel helper phage that improves phage display selection efficiency by preventing the amplification of phages without recombinant protein - Kramer, R. Arjen (Oxford University Press, 2003)
Phage display is a widely used technology for the isolation of peptides and proteins with specific binding properties from large libraries of these molecules. A drawback of the common phagemid/helper phage systems is the high infective background of phages that do not display the protein of interest, but are propagated due to non-specific binding to selection targets. This and the enhanced growth rates of bacteria harboring aberrant phagemids not expressing recombinant proteins leads to a serious decrease in selection efficiency. Here we describe a VCSM13-derived helper phage that circumvents this problem, because it lacks the genetic information for the infectivity domains of phage coat protein pIII. Rescue of a library with this novel CT helper phage yields phages that are only infectious when they contain a phagemid-encoded pIII-fusion protein, since phages without a displayed protein carry truncated pIII only and are lost upon re-infection. Importantly, the CT helper phage can be produced in quantities similar to the VCSM13 helper phage. The superiority of CT over VCSM13 during selection was demonstrated by a higher percentage of positive clones isolated from an antibody library after two selection rounds on a complex cellular target. We conclude that the CT helper phage considerably improves the efficiency of selections using phagemid-based protein libraries.